USE FINANCIAL TECHNOLOGY IN IMPROVING FINANCIAL LITERACY (EMPIRICAL STUDY ON FEB- UTP SURAKARTA STUDENTS) - Rahmatya Widyaswati; Supartini Supartini; Syahriar Abdullah; Achmad Choerudin; Istinganah Eni Maryanti (Jurnal Ekonomi, 2023)
This study will focus on students understanding and interest in fintech, how to use financial technology to increase students' financial literacy at the Faculty of Economics and Business, Universitas Tunas Pembangunan Surakarta, Central Java, Indonesia. The research method used is a qualitative descriptive analysis by analyzing, describing and summarizing various conditions, and situations from data collected in direct interview results. The results of this study are that students experience increased financial literacy by using financial technology. Students are used to using financial technology applications, most of which are used for payments. Students feel the use of financial technology helps in planning finances and investing. Financial literacy that plays a role in students is limited to their financial planning. Technology becomes their support in financial planning.